An observational study of various drug promotional advertising brochures: with an emphasis on World Health Organization ethical criteria for medicinal drug promotion - Dass, Ervilla (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drug promotional literature (DPLs) is an integral approach of pharmaceutical marketing strategy, which can almost influence a physician to prescribe definite variety of medicine from a particular company. The objective was to evaluate the accuracy, consistency, and validity of the information in accordance with the World Health Organization (WHO) ethical criteria for medicinal drug promotion. Methods: This was an observational study, in which total 100 DPLs were sorted out to evaluate whether the information is consistent/relevant with that presented by the criteria laid down by the WHO guidelines; such as nature of claims, pictorial content presented, cited references, the indication and significance of various data such as figure, graphs, table and clinical data. Results: From all the 100 promotional literatures sorted out, all showed the INN name and brand name, amount of active ingredient, dosage form and name and address of manufacturers/distributers was shown in all; adjuvants known to cause problem were not shown. Moreover, approved therapeutic uses were clearly mentioned in 35, 48 were having pictures presented, scientific graphs and clinical data were shown in 19. Conclusions: The results reveal that, majority of DPLs satisfied only half of the WHO criteria for rational drug promotion and none of them fulfilled all the specified criteria. Incomplete or exaggerated information in DPLs may mislead and result in irrational prescription. Therefore, physicians should critically evaluate DPLs regarding updated scientific evidence required for quality patient care.